(3Odjd GSJNOGe eYGjjQ GdeMGSHIs - (3MeGO, WGQb YHO GdYGds (2009)
(3jTJed Ydi GdeYGjjQ ef (B1 (3Edi (B30.s
(3HHdjhLQGajI (B: (3U(B. 557-558.s
(3aj (B: (3Odjd GSJNOGe eYGjjQ GdeMGSHI(B. -(3W(B. 1. -[(3GdEScfOQjI, eUQ(B] : (3GdOGQ GdLGeYjI, (B2009. -(3eL(B. 1.s
Keywords: (3GdeMGSHIs -- (3eYGjjQs